Assessment and treatment strategies for rotator cuff tears. Issue 2 (April 2015) - Al-Hakim, Wisam; Noorani, Ali; Lambert, Simon
Tears of the rotator cuff are common and becoming an increasingly frequent problem. There is a vast amount of literature on the merits and limitations of the various methods of clinical and radiological assessment of rotator cuff tears. This is also the case with regard to treatment strategies. Certain popular beliefs and principles practiced widely and the basis upon which they are derived may be prone to inaccuracy. We provide an overview of the historical management of rotator cuff tears, as well as an explanation for how and why rotator cuff tears should be managed, and propose a structured methodology for their assessment and treatment.